URBAN SUFISM: SPIRITULITY EDUCATION FOR MIDDLE CLASS MUSLIM - Wakhid Hasyim; Ahmad Syafii; Arifah Fauziah (FORUM PAEDAGOGIK, 2022)
The development of civilization does not mean ending the need for spirituality. The development of technology and the increasingly independent human life does not mean that the presence of God is not a necessity. Even amidst the increasingly glamorous millennial life, the need for spirituality is increasing. Islamic pop culture is followed by a religious spirit that is increasingly becoming the keyword and nowadays the need for spirituality is even more visible. In the midst of the aridity of worldly life, Sufism is an alternative answer by some classes of Muslim society. This research tries to explore how the development of urban Sufism is currently developing in our society. This type of research is literary research (library). Primary and secondary data sources are used as data. The results of the study show that the identity of middle-class Muslims in urban areas is experiencing a new chapter in the world of Sufism. Precisely after the New Order, along with the flow of globalization that gave birth to modernism, the urban middle-class Muslim Sufism movement appeared as the antithesis of the previously established conventional tarekat movement.